Influence of finishing diet on fatty acid profiles of intramuscular lipids, triglycerides and phospholipids in muscles of the Iberian pig. (Meat science, 1997)
Thirty Iberian × Duroc pigs allotted in groups of ten animals were fed in three traditional different management systems ('Montanera' (MO), fed on acorns; 'Recebo' (RE), fed on acorns and a commercial diet; and 'Cebo' (CE), fed on a commercial diet). Masseter muscle was obtained to evaluate the influence of management system on fatty acid (FA) composition of lean. The FA composition of the intramuscular total lipids, triglyceride (TG) and phospholipid (PL) fractions was evaluated. Muscle from MO pigs had greater quantities of monounsaturated fatty acids (MUFA) in the total lipids, triglyceride and phospholipid fractions than the other feedings. The percentage of saturated fatty acids (SFA) of i.m. total lipids and TGs increased (P < .05) with duration of feeding on RE and CE, from 35.13-35.10% in MO pigs to 37.47-37.84% in RE pigs and 39.98-41.11% in CE pigs. PLs from RE and CE pigs contained more C(18:2) and C(20:4) and less C(18:1) than MO pigs.